KAJIAN LITERATUR PENGUATAN KARAKTER BERBASIS KEARIFAN LOKAL SUNDA DI SEKOLAH DASAR - Muhamad Zulfi Tz (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character education is a fundamental aspect of the implementation of basic education, particularly in addressing the challenges of globalization and modernization that have led to shifts in students’ moral values. This article aims to examine in depth the concept of ethnopedagogy as an educational approach based on Sundanese local wisdom within the context of implementing the Merdeka Curriculum in elementary schools. This study employs a descriptive qualitative approach using a literature review method of various relevant scholarly articles published between 2016 and 2025. The findings indicate that Sundanese local wisdom values—such as cageur (healthy), bageur (kind), bener (righteous), singer (active), and pinter (intelligent)—have strong relevance to the dimensions of the Pancasila Student Profile. The integration of these values through traditional games, communal traditions, and storytelling media has been shown to strengthen students’ character in a contextual and sustainable manner. Therefore, ethnopedagogy based on Sundanese local wisdom can be considered an alternative strategy for strengthening character education in elementary schools.